Efficiencies and mechanisms of steel slag with ferric oxides for removing phosphate from wastewater using a column filter system - Ahmad, Siti Zu Nurain; Al-Gheethi, Adel; Hamdan, Rafidah; Othman, Norzila (Springer, 2020)
The current study aimed to investigate the efficiencies and mechanisms of slag filter media for removing phosphorus from synthetic wastewater. The steel slag with high ferric oxides (Fe2O3) was subjected for the electric arc furnace (EAF) and selected as the filter media (HFe). The chemical characteristics of HFe were determined using pH, point of zero charge (PZC) and XRF. The phosphorus removal efficiency was studied in a designed vertical steel slag column rock filters in unaerated HFe (UEF) and aerated HFe (AEF) system. The microstructure of HFe was analyzed by FTIR, XRD and SEM-EDX analysis. The results of XRF revealed that ferric oxide (Fe2O3) ranged from26.1 to 38.2%. PZC for Filter HFe was recorded at pH 10.55 ± 0.27. The highest efficiencies were recorded by UEF and AEF systems at pH 3 and pH 5 (89.97 ± 4.02% and 79.95 ± 6.25% at pH 3 and 72.97 ± 8.38% and 66.00 ± 12.85% at pH 5 for UEF and AEF, respectively). These findings indicated that AEF exhibiting higher removal than UEF systems might be due to presence high Fe concentration in AEF which play important role in the phosphorus removal. The main elements available on the surface of HFe included carbon, oxygen, iron, calcium, magnesium, silicon, platinum, sulphur, manganese, titanium and aluminium. The XRD analysis indicated that the precipitation of orthophosphate as calcium and iron-phosphates was the removal mechanism as confirmed using FT-IR analysis. These findings demonstrated the efficiency of HFe in removing of phosphorus from wastewater.